2021
DOI: 10.3389/fncel.2021.635486
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation and Infection in Age-Related Neurodegenerative Diseases: Lessons From Bacterial Meningitis Applied to Alzheimer Disease and Age-Related Macular Degeneration

Abstract: Age-related neurodegenerative diseases, such as Alzheimer disease (AD) and age-related macular degeneration (AMD), are multifactorial and have diverse genetic and environmental risk factors. Despite the complex nature of the diseases, there is long-standing, and growing, evidence linking microbial infection to the development of AD dementia, which we summarize in this article. Also, we highlight emerging research findings that support a role for parainfection in the pathophysiology of AMD, a disease of the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 109 publications
0
11
0
2
Order By: Relevance
“…In patients with AD both the onset and the progression of the disease has been associated with a history of infection in the patient’s life; in particular, the incidence of pneumonia, as well as respiratory and urinary tracts infections, has been shown to be higher in AD patients, traditionally considered a consequence of the disease, but can also be related to its onset (Kountouras et al, 2006 ; Natalwala et al, 2008 ; Miklossy, 2011 ; Too et al, 2021 ). Delirium, on the other hand, often caused by CNS infection, is correlated with an acceleration in the progression towards dementia (McManus and Heneka, 2017 ).…”
Section: Infection Burden and The Epidemiology Of Dementiamentioning
confidence: 99%
“…In patients with AD both the onset and the progression of the disease has been associated with a history of infection in the patient’s life; in particular, the incidence of pneumonia, as well as respiratory and urinary tracts infections, has been shown to be higher in AD patients, traditionally considered a consequence of the disease, but can also be related to its onset (Kountouras et al, 2006 ; Natalwala et al, 2008 ; Miklossy, 2011 ; Too et al, 2021 ). Delirium, on the other hand, often caused by CNS infection, is correlated with an acceleration in the progression towards dementia (McManus and Heneka, 2017 ).…”
Section: Infection Burden and The Epidemiology Of Dementiamentioning
confidence: 99%
“…In contrast, the other may/may not combine these peripheral signals with the effects of CD8 + T-lymphocytes recruited into the brain during the acute infection and which are retained after bacteria have been eliminated. The ability to identify and measure these differences experimentally is a key step towards understanding the means by which different infections exert neuro-toxic actions and will give insight towards developing effective therapies for ameliorating cognitive decline after infection and other related conditions ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, significant increases in the levels of inflammatory cytokines (TNFα, IL-6, and IL-1β) were observed in BPF-treated brains, which further confirmed the occurrence of neural inflammation. Neuroinflammation has been generally recognized as a factor negatively regulating neurogenesis and regeneration, and mammalian assays have suggested that the release and accumulation of inflammatory factors in the neural system parallel the cognitive dysfunction induced by neurodegenerative diseases, bacterial infection, and surgery. Therefore, we considered the abnormal cognitive behaviors of BPF-treated zebrafish associated with the activation of immune cells and neuroinflammation. A previous study also indicated that embryonic BPF exposure results in neural inflammation by activating microglia and then results in the abnormal behavioral response of zebrafish larvae .…”
Section: Discussionmentioning
confidence: 99%